Pembuatan Indeks Koleksi Keramik di Museum Adityawarman - Bivo Nevando; Desriyeni Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed how the process of making ceramics collection index as a means of information retrieval in Adityawarman Museum. This paper aims to describe the process of making ceramics collection index contained in Adityawaraman Museum. Their index ceramics collection is certainly going to provide convenience to visitors in search of information about ceramics is needed quickly and accurately. The method of writing this paper uses descriptive qualitative methods and instruments used to obtain data on interviews, observation or direct research of ceramic collections in Museum Adityawarman. From the data analysis through direct observation and documentation, collected as many as 279 collections from 22 different forms / ceramic names contained in Adityawarman Museum. Based on the results, it can be concluded that the index creation takes steps consisting of: (a) track and classify the type of ceramic collections, arranged alphabetically by the name of the collection; (B) the manufacture of ceramic collection description, the name of the collection, place of origin, size of the collection, the type of material, code and registration number of collection; (C) preparation of ceramic index by type and name; (E) the manufacture of ceramic collection index, the index title (the name of a collection of ceramics).Keywords: Manufacture, Indexes Ceramic Collection.